Renormalization of the pseudoscalar operator at four loops in QCD - Long Chen; Michał Czakon; Marco Niggetiedt (Journal of High Energy Physics)
Abstract We present the renormalization constant of the pseudoscalar operator defined with a non-anticommuting γ 5 in dimensional regularization up to four-loop order in perturbative Quantum Chromodynamics (QCD). Furthermore, by virtue of renormalization-group invariance of the relation between the scalar and the pseudoscalar operator, we predict the MS ¯ $$ \overline{MS} $$ factor of the renormalization constant for the latter at five-loop order in QCD.